Processing XML with Java : a guide to SAX, DOM, JDOM, JAXP, and TrAX - Harold, Elliotte Rusty (Addison-Wesley, 2003)
Java is the ideal language for processing XML documents. Consequently, more XML tools have been written in Java than in any other language. More open source XML tools are written in Java than in any other language. Processing XML with Java fills an immediate need for developers who are working with XML in Java. It is a comprehensive tutorial and reference to the major APIs. This book shows developers how to: save XML documents from their applications written in Java; read XML documents produced by other programs; communicate with network servers that send and receive XML data; validate documents they receive against DTDs, schemas, and business rules; and integrate XSLT into their programs.